Chemometric study of thermal treatment effect on the P25 photoactivity for degradation of tartrazine yellow dye. Issue 11 (1st August 2018) - Souza, Isis P.A.F.; Pezoti, Osvaldo; Bedin, Karen C.; Cazetta, André L.; Melo, Sandra A.R.; Souza, Lucas S.; Silva, Marcela C.; Almeida, Vitor C.
Abstract: In the present work, a chemometric study was carried out using a central composite rotatable design (CCRD) to evaluate the effect of thermal treatment on the P25 photoactivity for degradation of tartrazine dye. The factors investigated for thermal treatment were: temperature, heating rate and heating time, and the experimental design response was the photodegradation constant ( k app ). The response surface methodology (RSM) was employed to obtain the material with higher k app value for tartrazine photodegradation, under UV radiation, and investigate the interactions between factors of thermal treatment. The P25 used as precursor, as well as the obtained material from the optimized conditions (TTPop ), and the material with worst photocatalytic activity (TTP-17) were characterized from the N2 physiosorption, FT-IR, SEM, XRD, DSC/TGA and PAS. The TTPop was obtained under conditions of temperature of 298 °C, heating rate of 10 °C min −1 and heating time of 177 min. TTPop showed k app value of 25.7, while P25 and TTP-17 presented k app values of 20.2 and 10.0, respectively. Graphical abstract: fx1